Documents from F. Taylor Ostrander - Samuels, Warren J., 1933-; Ostrander, F. Taylor (Emerald, 2005)
Volume 23B of this research annual presents eight sets of lecture notes taken in 1933-4 by F. Taylor Ostrander at the University of Chicago. The notes are from courses given by Frank H. Knight, Henry C. Simons, and Melchior Palyi. The materials provide insight into the first generation of the Chicago School.
Keywords: Economics -- Study and teaching (Higher); Economics -- Methodology.; Economics -- Research.; elektronické knihy; electronic books